In Vitro Biodegradation of a-C:H:SiOx Films on Ti-6Al-4V Alloy; Materials; Vol. 15, iss. 12 - Grenaderov A. S. Aleksandr Sergeevich; Solovyev A. Andrey; Oskomov K. V. Konstantin Vladimirovich; Porokhova E. Ekaterina; Brazovsky (Brazovskii) K. S. Konstantin Stanislavovich; Gorokhova A. V. Anna Viktorovna; Nasibov T. Temur; Litvinova L. Larisa; Khlusov I. A. Igor Albertovich (2022, 2022)
Title screen